Study of Cocoa Farmers' Motivation (Thebroma Cacao) as an Effort to Improve the Welfare of Farming Communities in Rakadua Village, Bombana Regency - Herlinda, Herlinda (USN Kolaka, 2023)
Farmers try to have other jobs to meet household needs. The total income of farmer households measures the welfare of the farming community, both income obtained from cocoa farming activities and activities other than cocoa farming. Farmers will spend this total income to meet their various life needs. This study aimed to determine the motivation of cocoa commodity farmers to improve welfare in Rakadua Village, Poleang Barat District, and Bombana Regency. The type of research used is quantitative research. The results of the study showed that the average farmer's motivation assessment was high because each farmer has motivation such as the responsibility of each farmer so that they know what they have to do so that their desired goals can be achieved, namely to be able to develop farming well to get more profit and 75 samples of cocoa farmers in Rakadua Village are included in the prosperous category because the income they receive can meet their family needs such as food, clothing, and children's education. The results of the data analysis show an average value of farmer motivation of 76.9% and an average value of farmer welfare of 78.7%, with each categorized as high, which means that the higher the farmer motivation, the higher the level of welfare of farmers in Rakadua Village. Work motivation itself is supported by indicators that drive motivation to increase welfare.